2016
DOI: 10.3389/fnsys.2016.00063
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of Cyclophilin-D Provides Partial Amelioration of Intrinsic and Synaptic Properties Altered by Mild Traumatic Brain Injury

Abstract: Mitochondria are central to cell survival and Ca2+ homeostasis due to their intracellular buffering capabilities. Mitochondrial dysfunction resulting in mitochondrial permeability transition pore (mPTP) opening has been reported after mild traumatic brain injury (mTBI). Cyclosporine A provides protection against the mPTP opening through its interaction with cyclophilin-D (CypD). A recent study has found that the extent of axonal injury after mTBI was diminished in neocortex in cyclophilin-D knockout (CypDKO) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 94 publications
1
15
0
Order By: Relevance
“…Pyramidal neurons are the major excitatory component in cortical networks (Fairen et al, 1984 ; DeFelipe and Fariñas, 1992 ; Somogyi et al, 1998 ). Previously we showed that intact YFP+ pyramidal neurons intrinsic and extrinsic/synaptic properties were altered post-mTBI and developed over time (Greer et al, 2012 ; Hånell et al, 2015a ; Sun and Jacobs, 2016 ). Initially after mTBI, the intrinsic properties of intact pyramidal neurons paralleled that found in the DAI population, suggesting that ion and/or neurotransmitter imbalance had an indiscriminant overriding effect on currents (Greer et al, 2012 ).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Pyramidal neurons are the major excitatory component in cortical networks (Fairen et al, 1984 ; DeFelipe and Fariñas, 1992 ; Somogyi et al, 1998 ). Previously we showed that intact YFP+ pyramidal neurons intrinsic and extrinsic/synaptic properties were altered post-mTBI and developed over time (Greer et al, 2012 ; Hånell et al, 2015a ; Sun and Jacobs, 2016 ). Initially after mTBI, the intrinsic properties of intact pyramidal neurons paralleled that found in the DAI population, suggesting that ion and/or neurotransmitter imbalance had an indiscriminant overriding effect on currents (Greer et al, 2012 ).…”
Section: Discussionmentioning
confidence: 95%
“…Specifically, following experimental mTBI using transgenic mice, we observed primary neocortical damage involving scattered DAI within a subset of layer 5 pyramidal neurons expressing a yellow variant of green fluorescent protein (YFP) labeling the soma as well as their dendrites and axons (Greer et al, 2011 ). Perhaps even more biologically significant was our parallel observation that the non-DAI (intact) YFP+ neuronal population showed altered electrophysiological properties without any evidence of overt structural damage (Greer et al, 2012 ; Hånell et al, 2015a ; Sun and Jacobs, 2016 ). Over time, these same intact YFP+ pyramidal neurons became hyperexcitable, entirely consistent with some form of mTBI-induced circuit disruption within local neocortical networks (Zhang and Raichle, 2010 ; Wolf and Koch, 2016 ).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The expression of CypD was elevated in brain tissues of Alzheimer's disease (AD) transgenic mice (Du et al, 2008(Du et al, , 2011(Du et al, , 2014, which promotes AD neuropathogenesis (Wang et al, 2009;Zhu et al, 2013;Adiele and Adiele, 2016). Knockout (KO) of CypD stabilized mitochondrial function (Du et al, 2008(Du et al, , 2011(Du et al, , 2014Gainutdinov et al, 2015;Gordan et al, 2016;Sun and Jacobs, 2016), decreased threshold of mPTP formation, and improved cognitive function in old AD transgenic mice (Du et al, 2008(Du et al, , 2011(Du et al, , 2014. However, the role of CypD in the developmental anesthesia neurotoxicity remains largely to be determined.…”
Section: Introductionmentioning
confidence: 99%